Cute-Bri: Exploring Cultural Authenticity Resource Role in Driving Competitive Advantage - Putra, Febrianur Ibnu Fitroh Sukono; Panjaitan, Roymon; Fatmawati, Elia Resha; Rumanti, Seline Widi (Universitas Islam Nahdlatul Ulama Jepara, 2025)
Objective: This study investigates the mediating role of cultural heritage authenticity in enhancing competitive advantage through cultural innovation capital among SMEs producing traditional products. Research Design & Methods: Data were collected from 372 SMEs in Central Java using a structured questionnaire with a 5-point Likert scale, and analyzed using Structural Equation Modeling―Partial Least Squares (SEM-PLS) with SmartPLS 3.0. Findings: The results indicate that cultural heritage authenticity significantly influences both cultural innovation capital and competitive advantage, with cultural innovation capital acting as a key mediator that enables SMEs to maintain cultural authenticity while adapting to modern market demands. Additionally, cultural innovation capital enhances SMEs’ ability to strategically innovate while preserving cultural values, thus providing a competitive edge. Implications and Recommendations: The findings suggest that SMEs should incorporate culture-based innovation strategies, leveraging cultural innovation capital to navigate the balance between tradition and modernization. Policymakers should support such efforts through specialized training programs and resource allocation to facilitate innovation without compromising cultural integrity. Contribution & Value Added: This study makes several important scientific contributions. First, this research advances customer culture theory by exploring the dynamic relationship between cultural authenticity, innovation, and competitive advantage in the context of SMEs producing traditional products. Second, this research provides practical implications for SMEs and policymakers in balancing cultural preservation with market-driven innovation. This research enriches the literature on cultural entrepreneurship and contributes to the growing body of knowledge on the intersection of culture and business strategy, particularly in emerging economies.